NORARTOCARPETIN, FLAVONE DERIVATIVE FROM LEAVES OF Artocarpus fretessi - Nunuk Hariani Soekamto; Nursiah La Nafie; Fredryk Welliam Mandey; Marry Garson (Indonesian Journal of Chemistry, 2009)
Norartocarpetin (1), together with mulberrin (2) and mulberrokromen (3) were isolated from Artocarpus fretessi (Moraceae). This plant is an endemic species in Indonesia and locally known as ";Kelembi"; or ";Maumbi";. The structure of these compounds were elucidated on the basis of physical and spectroscopic data. Compounds (1) is precursor of compound (2) and (3) in the biogenetic pathway.